On Dual Hyperbolic Generalized Woodall Numbers - , Orhan Eren; , Yuksel Soykan (Archives of Current Research International, 2024)
In this work, we introduce the generalized dual hyperbolic Woodall numbers. As special cases, we study with dual hyperbolic Woodall, dual hyperbolic modified Woodall, dual hyperbolic Cullen numbers and dual hyperbolic modified Cullen numbers. Also, we present Binet’s formulas, generating functions, some identities, linear sums and matrices related with these sequences. In addition, we give Catalan’s and Cassini’s identities.